GENERAL EDUCATION AND SPECIAL EDUCATION: HARMONIZATION OF INCLUSIVE EDUCATION TOWARDS K-12 SYSTEM IN THE PHILIPPINES (Proceedings of International Conference on Special Education, 2015)
In April 2014, a four-day workshop entitled Inclusive Education Harmonization Project was conducted among DepEd officials and representatives from different regions to collect information on IE conceptualization and practices in the Philippines. This sought to evaluate the existing policies and service delivery modalities to arrive at strategic actions towards strengthening and implementing IE in the country. Responsive to the transition of Philippine Basic Education to K-12 system, the study aligned its evaluation on the K-12 provisions on inclusiveness. Data gathered were analyzed to identify policies and practices supportive of IE and come up with recommendations for IE implementation. The desire for IE is expressed implicitly in the IRR of K-12. Its provision for inclusiveness is evident in Section 8 which states that the learners’ cultural background and special needs should be taken into consideration. Meanwhile, Article 12 of the Policies and Guidelines in SPED in the Philippines in 1998 echoed a clear recommendation of passing legislative measures on IE. DepEd initiated a more concrete action for IE by releasing DepEd Memo No. 373, s. 2009, which details a comprehensive inclusive program for children with special needs. Results established that Special Education and General or Basic Education as a field has earned autonomy over the years. The action of GenEd and SPED to the call for IE seemed uneven in terms of time and extent. Furthermore, some policies in GenEd and SPED were found to pose a challenge towards IE. Similarities and differences of these two fields in terms of eight domains, namely, learners, governance, curriculum, instruction, teacher or professional development, assessment, environment, and sustainability, were established to identify and overcome challenges and issues at hand. Autonomy enabling factors such as historical data, legal mandates and funding streams were reviewed to come up with a unifying plan of action towards IE in the Philippines as response to IE global movement.